2000
DOI: 10.1103/physrevb.62.16600
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the energy and broadening parameter of the fundamental band gap of GaSb andGa1xInx

Abstract: We have measured the temperature dependence of the energy ͓E 0 (T)͔ and broadening parameter ͓⌫ 0 (T)͔ of the fundamental gap for GaSb and four samples of Ga 1Ϫx In x As y Sb 1Ϫy ͑lattice matched to GaSb͒ using infrared photoreflectance. The parameters that describe the temperature variation of the energy ͑including thermalexpansion effects͒ were evaluated using both the semiempirical Vashni relation as well as an equation that incorporates the Bose-Einstein occupation factor. The behavior of ⌫ 0 (T) was descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…1 Therefore, PR spectroscopy has found wide applications in characterizing materials' band structures in the last decades. [2][3][4][5] It is noteworthy, however, that up to now the studies have been mostly limited to the wide-band materials in visible and near infrared spectral regions with a wavelength shorter than 4 m. 6,7 This limitation is due mainly to the facts that ͑i͒ the source in the mid-to far-infrared spectral region produces far fewer photons than the tungsten filament lamps, and ͑ii͒ the long-wavelength photodetector, e.g., HgCdTe, is inherently less sensitive than the Si-or InGaAs-based visible-region one. The joint effect of the source and the detector makes the inefficiency of grating spectroscopy increasingly important.…”
Section: Photomodulated Infrared Spectroscopy By a Step-scan Fourier mentioning
confidence: 99%
“…1 Therefore, PR spectroscopy has found wide applications in characterizing materials' band structures in the last decades. [2][3][4][5] It is noteworthy, however, that up to now the studies have been mostly limited to the wide-band materials in visible and near infrared spectral regions with a wavelength shorter than 4 m. 6,7 This limitation is due mainly to the facts that ͑i͒ the source in the mid-to far-infrared spectral region produces far fewer photons than the tungsten filament lamps, and ͑ii͒ the long-wavelength photodetector, e.g., HgCdTe, is inherently less sensitive than the Si-or InGaAs-based visible-region one. The joint effect of the source and the detector makes the inefficiency of grating spectroscopy increasingly important.…”
Section: Photomodulated Infrared Spectroscopy By a Step-scan Fourier mentioning
confidence: 99%
“…The dotted lines in Fig. 2 represent the theoretically predicted position of these spectra, i.e., for an ideally rectangular QW profile [23][24][25][26], which results from several composition-related effects. The primary influence on the ground state transition energy shift is attributed to the As-induced band gap change [27].…”
Section: Resultsmentioning
confidence: 99%
“…Wang and co-workers 11 found room temperature tunable blue-green photoluminescence in nanocrystalline PST films under ultraviolet ͑UV͒ excitation. 14 In spite of these work, there are scarce open literatures on the temperature dependence of optical response of PST films, especially near fundamental band gap regions ͑i.e., absorption regions͒, which not only avails design, optimization and evaluation of PST-based photoelectric devices but also may provide many important physical information about the temperature dependent evolution of band gap and electron transition, band tail state behaviors, excitonic effects and even the electron-phonon interactions, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] and thus enrich the related physics mechanisms in ferroelectric films. To obtain the key physical parameters critically for the applications of integrated optics, Verma et al and Liu et al reported the optical characteristics of PST films in the transparent region by Swanepoel model and Cauchy models, respectively.…”
Section: Temperature Dependent Optical Properties Of Mn Doped "Pb Srmentioning
confidence: 99%